RESPONSIBILITY FORMATION IN PRIMARY SCHOOL AGE CHILDREN - Irisa Saera Radzhabovna (American Journals, 2025)
This article emphasizes that it is much more important to form responsibility among younger students. It becomes most relevant from the moment a child enters school. Going to school means a drastic change in the child's entire lifestyle. It says how important responsibility is for a child to obey the rules of behavior and achieve academic results.
Keywords: Responsibility, accountability, behavior, skill, regime, strong-willed virtue